Clinical profile and cardiovascular autonomic function tests in patients with postural orthostatic tachycardia syndrome - Neeraj; Suchitra Deolalikar; Aman Pannu; Jeyaraj Durai Pandian (Wolters Kluwer Medknow Publications, 2019)
Background: Postural orthostatic tachycardia syndrome (POTS) is an autonomic disorder characterized by the clinical symptoms of orthostatic intolerance such as light-headedness, fatigue, sweating, tremor, anxiety, palpitation, exercise intolerance, and near syncope on standing in the absence of orthostatic hypotension. Objective: The objective of this study is to evaluate the clinical profile and autonomic parameters in patients with POTS. Materials and Methods: A total of 70 patients with POTS underwent cardiovascular autonomic function tests, i.e., heart rate (HR) response to deep breathing, heart rate and blood pressure (BP) changes in Valsalva maneuver and tilt study in the autonomic laboratory of the Department of Neurology from January 2014 to February 2016 using WR Medical Works, USA. Results: Mean age of cohort was 28.07 ± 10.64 years, and there were 36 (51%) women. Light-headedness 59 (84.3%) was the most common orthostatic symptom, followed by dizziness 56 (80%), palpitation 41 (58.57%), anxiety 26 (37.14%), loss of consciousness 21 (30%), disequilibrium 19 (27.14%), visual symptoms 12 (17.14%), weakness 8 (11.43%), and shortness of breath 2 (2.86%). The average heart rate response to deep breathing was 24.79 ± 7.20 bpm. Average Valsalva ratio was 1.78 ± 0.30. During the tilt, average maximum HR increase was 43.47 ± 11.19 bpm. Conclusion: POTS is an underrecognized disorder and majority of them present with vague orthostatic symptoms ways, hence clinicians should be made aware of the symptomatology. The tilt table test with beat-to-beat monitoring of HR and BP is the standard test for diagnosis.